Ethics in Communicating Between Students and Lecturers via WhatsApp: A Study of 1st Semester Civics Students at Mataram University - Rahmi; Tri Armelia; M. Khaekal Yunanda; Lista Mandaliana; Agung Wahyudi; Zelin Sabila; Moh. Syawalluddin; Edy Herianto (al-Afkar, Journal For Islamic Studies, 2025)
WhatsApp is a conversation application that is widely used as a communication medium between students and lecturers in an academic environment. When using WhatsApp, you need to pay attention to appropriate communication etiquette. The guide used in this research is the communication ethics guide at Mataram University. The aim of this research is to examine the ethics of communication between students and lecturers via the WhatsApp application, especially for first semester students of the Pancasila and Citizenship Education Study Program (PPKn) FKIP, Mataram University. The method used in this research is descriptive qualitative and data collection is carried out through observation, interviews and documentation. The results of the research show that there are still violations of communication ethics among PPKn 1st semester students at Mataram University, such as not paying attention to time, not introducing themselves, using impolite language, and sending repeated messages (spam). The problem of violations of communication ethics is caused by students' lack of understanding about good communication ethics and their urgent needs in lectures. Therefore, there needs to be an emphasis on the importance of implementing communication ethics in order to create harmonious relationships in the educational environment. It is hoped that the results of this research can become a reference in increasing awareness of communication ethics among students.